Strategi Pemerintah Dengan Pelaku Bisnis Dalam Mengoptimalkan Pasar Halal Di Jepang - Thamrin, Muhammad; Robihim, Robihim (GEMA EKONOMI, 2023)
Currently, Japan's free market and industrial economy is the third largest in the world after the United States and China, in terms of international purchasing power variations. The Japanese economy is made up of all the elements that make up a modern economy: industry, trade and agriculture. Good relations with various countries are one of the factors that help expedite foreign trade. One of them that is being intensively reviewed by the Japanese government is the halal market in Japan which has experienced quite significant developments in recent years. The Japanese government is motivated to advance the halal market by increasing the halal industry and halal tourism because Muslim tourists from all over the world are starting to flock to Japan. The seriousness of the Japanese government in the halal market is marked by the provision of halal-certified products that attract Muslim tourists from all over the world. Japan is also paying attention to the application of sharia principles in the field of tourism, including halal food with halal standards. The desire to prepare many halal restaurants was also driven by Japan's election as host for the world sporting event, the 2020 Olympics.